2018
DOI: 10.1108/ijppm-06-2016-0108
|View full text |Cite
|
Sign up to set email alerts
|

The complex influences of quality management leadership and workforce involvement on manufacturing firm success

Abstract: Purpose Quality management constructs related to management leadership and workforce involvement have consistently shown strong correlation with firm success for years. However, there is an increasing body of research based on complexity theory (CT) suggesting that constructs such as these should be viewed as variables in a complex system with inter-dependencies, interactions, and potentially nonlinear relationships. Despite the significant body of conceptual research related to CT, there is a lack of methodol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…These leadership attributes are compatible with a TQM environment; as such, it has been suggested that TFL is the type of leadership that is more suitable for effective TQM implication (Dean and Bowen, 1994; Idris and Mohd Ali, 2008; Waldman, 1994; Rui et al , 2010). The literature also supports that TFL increases employee engagement (Popli and Rizvi, 2017) or involvement (Liu et al , 2011; Welty et al , 2014), which is vital for the effective and universal implementation of TQM philosophy (Formby et al , 2018).…”
Section: Introductionmentioning
confidence: 96%
“…These leadership attributes are compatible with a TQM environment; as such, it has been suggested that TFL is the type of leadership that is more suitable for effective TQM implication (Dean and Bowen, 1994; Idris and Mohd Ali, 2008; Waldman, 1994; Rui et al , 2010). The literature also supports that TFL increases employee engagement (Popli and Rizvi, 2017) or involvement (Liu et al , 2011; Welty et al , 2014), which is vital for the effective and universal implementation of TQM philosophy (Formby et al , 2018).…”
Section: Introductionmentioning
confidence: 96%
“…Although the alignment of actors in relation to the overall network objectives is required, the self-organized behavior within the network can yield value by synchronizing purpose and actions (Silva and Guerrini, 2018). Similarly, Bergquist et al (2019) maintain that self-organization contributes to maximizing benefits in the long run, while Formby et al (2018) empirically corroborate that self-organization is a significant predictor of business success. Therefore, we postulate that: H4.…”
Section: Effect Of Decentralized Information Technologies On Supply C...mentioning
confidence: 82%
“…purchasing, logistics, inventory management) contributes to operational efficiency and enhances responsiveness. On the other hand, Formby et al (2018) underscore that management is often non-reliant in formal authority, and thus, it may impede performance as self-organization emerges. As mentioned by Adobor and McMullen (2018), although self-organized firms with a high level of freedom to act independently seek to achieve individual goals, SCSO still benefits from a collective outcome.…”
Section: Effect Of Decentralized Information Technologies On Supply C...mentioning
confidence: 99%
“…The conceptual model, depicted in Figure 1, attempts at linking the CAS theory with the SCPV. In particular, we argue that relational performance at the triadic level leads to a success that lies beyond simple linear structures (Formby et al , 2018) and thus can be attributed to the CASs. Similarly, Harkema (2003) underscores that CASs manifest nonlinear and dynamic behavior.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 91%